Return-to-Play Timeline and Recovery Predictors After COVID-19 Infection in Elite Football Players - Agnes Sziva; Zsuzsanna Kives; Zsolt Szelid (Sports)
The pandemic period significantly impacted professional football, leading to mandatory SARS-CoV-2 testing and quarantine. Our study aimed to examine the factors influencing time of recovery after a positive test, including return-to-training (RTT) and return-to-first-match (RTFM) of male football players in a first-division Hungarian team between 8 May 2020 and 30 June 2022. Infection was determined using mandatory RT-PCR testing 3 times per week, which later decreased to 1 to 2 times per week, in 55 elite players. A self-administered questionnaire was utilized based on the U.S. Department of Health and Human Services symptom list and modified with relevant factors of return-to-play in football. The incidence of SARS-CoV-2-positive players in the three consecutive years was 5.26; 21.43 and 45.71%. Mild symptoms were present in test-positive players, completing the questionnaire (n = 31), predominantly loss of smell and dry cough. Post-infection fatigue levels correlated with the perceived performance decline. In players with precisely documented dates (n = 18), the average RTT was 18.7 days, while the RTFM was 67.3 days. Older players returned to training faster than their younger counterparts and the RT-PCR Ct number had a weak negative correlation with RTFM. Mental support was provided by family and friends in 68% of the players. This study highlights the variability in return-to-play timelines and the role of age, symptom severity and mental help in recovery and emphasizes the need for individualized rehabilitation in elite football.